Competencies in organizational e-learning : - Sicilia, Miguel-Angel (Information Science Pub., 2007)
Although they approach their subject from a variety of perspectives, the core issue addressed by the 16 papers presented here by Sicilia (U. of Alcalá, Spain) concerns the measurement of competencies in organizational learning technology and knowledge management systems. The papers address issues of definition; relationships; similarities or complementarities; and how to derive aggregated competency scores and figures for groups, departments, and organizations. They are presented in sections dealing with general concepts and management issues, competencies from the viewpoint of e-learning and organizational memory, and competencies and machine-understandable semantics for the Web.